Load shedding and its crippling effect on the South African economy: an entrepreneurial perspective - Pillay, The Arianna; Beharry-Ramraj, Andrisha (Penerbit Universiti Kebangsaan Malaysia, 2024)
The country has experienced industry shutdowns, decreased productivity, educational setbacks, increased unemployment rates, and negative healthcare outcomes. Load-shedding in South Africa is primarily caused by inadequate maintenance, internal mismanagement, corruption, and a lack of skills. This issue has had a significant impact on small businesses, as they often lack the necessary resources to handle power surges, equipment damage, and the costs associated with replacing stock. This paper explores how load-shedding has impacted the South African economy from an entrepreneurial perspective. The research is qualitative and exploratory in nature, and it was found that load-shedding has had a significant impact on businesses' finances, resources, and performance. Load-shedding in South Africa has had a severe impact on the daily lives of people, causing disruptions in businesses, households, and the overall economy. Eskom, the primary supplier of energy in South Africa, has been facing significant challenges in meeting the growing demand for electrical energy, leading to job losses, decreased productivity, and a loss of billions of rands. Small businesses have been particularly affected, with an estimated 75% of them failing after being operational for less than three years due to load-shedding. To ensure small businesses have electricity to operate during load-shedding it is recommended that small businesses adopt alternative energy sources like solar power to increase the businesses’ independence and mitigate the effects of load-shedding. The South African government should also encourage and support small businesses to collaborate with successful renewable energy companies.